2009
DOI: 10.1007/s00380-008-1090-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between variants in the genes for leptin, leptin receptor, and proopiomelanocortin with chronic heart failure in the Czech population

Abstract: Patients with chronic heart failure (CHF) express enhanced catabolic metabolism finally resulting in overall weight loss, whereas adipokines might play a crucial role in signaling among tissues. The aim of this study was to investigate the possible associations of defined variability in leptin (dbSNP ID rs7799039), proopiomelanocortin (dbSNP ID rs3754860 and dbSNP ID rs1009388), and leptin receptor gene (dbSNP rs1137101) with CHF and evaluate their potential as the CHF susceptibility genes. The case-control st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 36 publications
0
16
0
2
Order By: Relevance
“…In the Finnish Diabetes Prevention Study, Salopuro et al found that two polymorphisms (Lys109Arg, Gln223Arg) in the extra-cellular domain of the leptin receptor predicted the conversion to T2DM in high-risk individuals with IGT(impaired glucose tolerance) [20]. Besides, the LEPR Gln223Arg polymorphism was also found to be a risk factor both in ischemic heart disease and dilated cardiomyopathy patients [21]. Further investigations were carried out to assess the association between LEPR Gln223Arg polymorphism and the risk of polycystic ovary syndrome.…”
Section: Discussionmentioning
confidence: 97%
“…In the Finnish Diabetes Prevention Study, Salopuro et al found that two polymorphisms (Lys109Arg, Gln223Arg) in the extra-cellular domain of the leptin receptor predicted the conversion to T2DM in high-risk individuals with IGT(impaired glucose tolerance) [20]. Besides, the LEPR Gln223Arg polymorphism was also found to be a risk factor both in ischemic heart disease and dilated cardiomyopathy patients [21]. Further investigations were carried out to assess the association between LEPR Gln223Arg polymorphism and the risk of polycystic ovary syndrome.…”
Section: Discussionmentioning
confidence: 97%
“…Heterozygosity confers mild hyperleptinemia and insulin resistance, with marked effects in homozygous mutant (fa cp /fa cp ) rats [83,86]. Notably, leptin administration has been shown to induce eccentric dilatation of the left ventricle [87], while leptin receptor polymorphisms and circulating leptin associate with human HF [88]. In contrast to 10-to 12-month-old SHRs with concentric hypertrophy, agematched lean male SHHF rats develop eccentric hypertrophy and lack ventricular wall thickening [89].…”
Section: Genetic Modelsmentioning
confidence: 97%
“…У більшості досліджень відмічається зв'язок поліморфізму гену LEPR Q223R з факторами кардіоваскулярного ризику -ожирінням, метаболіч-ним синдромом, дисліпідемією [6][7][8]. Засвідчений зв'язок поліморфізму гена LEPR Q223R з розвитком серцевої недостатності у хворих на ІХС та дилята-ційну кардіоміопатію [9]. В той же час, питання щодо поширеності та значення поліморфізму гену LEPR у хворих на ІХС за умов коморбідності з ЦД 2 типу, в тому числі в українській популяції, остаточно не з'ясовано.…”
Section: обґрунтування дослідженняunclassified
“…У польській популяц ії не виявлено суттєвих відміннос-тей за частотою г енотипів RR та QR між пацієнтами з ІМ (26,1 та 47,8 %), пацієнтами з ЦД 2 типу (23,2 та 51,6 %) та практично здоровими особами [14]. За резуль-татами обстеження 372 пацієнтів з хронічною серцевою недостатністю та 407 практично здорових осіб, жителів Чехії, поліморфіз м гену LEPR Gln223Arg більш, ніж втричі підвищував ризик прогресування серцевої не-достатності у пацієнтів чоловічої статі з ІХС (НR=3,15; 95 % CI 1,68-5,91 ) та дилятаційною кардіоміопатією (НR=3,5; 95 % CI 1,13-10,81) [9].…”
Section: обговорення результатів дослідженняunclassified